Sharia Cooperatives' Productive Waqf Management Model Through Financial Technology Services in Bandung City Area to Promote The People's Economy - Nurjamil; Siti Nurhayati (Publisher Cv. Inara, 2021)
Waqf continues to develop as a pillar of people's economic power, from the conventional land waqf concept of social and educational facilities to the modern enough stage, now known as cash waqf money, cash waqf linked sukuk (CWLS) and fintech linked to the waqf fundraising process. The aim of this study is to provide an understanding of the legal status of waqf producers, through the use of fintech applications in the context of Law No. 41 of 2004 on Waqf and Law No. 11 of 2008 on Electronic Information and Transactions, and through a processing methodology to find an economic empowerment model for people with productive waqf assets. The study uses a methodology which refers to qualitative legal research. Research findings concluded that Fintech apps are not properly regulated by Waqf of the ITE Law, but are still permitted to be used in the management of cash waqf as long as they are not in breach of the law in force. In the management of waqf, Nazhir shall be liable and may be prosecuted in the event of a loss of waqf properties due to its negligence. Sharía Cooperatives registered as cash waqf nazhir and in cooperation with Bandung City Fintech companies are owned by BMT ITQAN only where they are financed by itqanmobile and involve the Fintceh platform kitawakaf.com with the help of the House Financing Assembly empowerment program for BMT member SMEs with waqf funds and the waqf management models